Public policy a concise introduction - Rinfret, Sara R.; Scheberle, Denise; Pautz, Michelle C. (CQ Press, an Imprint of SAGE Publications, Inc, 2023)
"Public Policy: A Concise Introduction is a student-friendly textbook that quickly connects readers to the inner workings of public policy. The text condenses early chapters on theory and the policy-making process, allowing students to take up key policy challenges - such as immigration, education, and healthcare - much earlier in the semester. Not every student starts out engaged in public policy, so place your students - both majors and non-majors alike - in the driver's seat by fostering their analytical skills early and spend the rest of the semester discussing policy issues, examining data, and debating current policy examples that matter most to them. The Second Edition has been updated to include how we can collectively use public policy to raise individuals from the margins and address inequities that exist in our system. Recent policy questions include: "How do we shape our country's health care system?", "How do we address increases in costs of tuition?", and "Did the COVID-19 pandemic positively or negatively shape our public education system?""--